Model of cash Waqf through salary deduction for financing higher education among academic staffs at UiTM Melaka / Nur Amalina Abdul Aziz and Sara Eliza Mansor - Abdul Aziz, Nur Amalina; Mansor, Sara Eliza (2014)
Waqf is one of the Islamic financial scheme that should be emphasizes to enhance Muslim economy. The connotations of waqf in Malaysia mainly focused towards cemetery land, mosque and building. However, researches shown that the awareness towards cash waqf is still behind compared to other countries such as Indonesia and Middle Eastern countries. Research indicates that cash waqf has the potential to promote the development of the ummah. The authors estimate that the cash waqf collection in Malaysia could reach RM4.3 billion a year if each Muslim adult Malaysian citizen donated RM1 a day or RM30 a month. This would generate significant economic opportunities for the Muslim community. Nevertheless, the management of cash waqf is important to avoid the misuse of the funds. Therefore, it is imperative to ensure that proposed model will consider the security of funds. This study particularly focuses on the characteristics of cash waqf, suggests a structure for cash waqf model through salary deduction, and studies the potential of the cash waqf model through salary deduction in financing higher education students. The expectation is that the model benefits both students and higher education institutions and hence, contributes to Malaysia becoming a high income nation with high labour qualification.